Inspection of the Level of Effects of Service Quality to Customer Satisfaction in Retail Supermarkets - Nguyen Thi Hang; Pham Minh Dat; Nguyen Van Huan; Truong Thi Viet Phuong (Budapest International Research and Critics University, 2020)
For every business dealing in goods and services, especially in the field of sales, attracting more and more buyers will help increase sales, contributing to achieving the ultimate goal of the producer. Profit maximization. Currently, retail supermarkets are facing fierce competition pressure among supermarket organizations: from the competition of existing supermarkets in the area, the chains of buffet goods, the shopping centers, the penetration of the